Análise das peculiaridades do trabalho do assistente social na proteção social básica da assistência social em Manaus: gestão e planejamento em questão - Mendonça, Carlos Raimundo Batista (Brasil, 2022)
Planning is an essential tool for the materialization of objective, effective and qualified actions that guarantee the effective fulfillment of social needs. The proposal in question has the general objective of analyzing the management and planning instruments of the Social Assistance Reference Centers - CRAS of Manaus/AM in 2019 to discuss the peculiarities of the work of the social worker in the scope of basic social protection, based on a survey documentary. The specific objectives are: 1) To know the instruments of management and planning of activities in the CRAS in the scope of the basic protection of the social assistance policy; 2) Discuss the private attributions of the social worker within the scope of the CRAS technical teams based on the regulations of the Social Service area; 3) Identify in the institutional plans and reports the sources of information used for the planning of activities in order to correlate the activities planned and executed in the CRAS. Regarding the methodological aspects, it is an explanatory research, with a qualitative and quantitative approach, using documental research to carry out the collection of data that were made available by the Social Assistance Reference Centers - CRAS of Manaus, and at the Municipal Secretary of Women, Social Assistance and Citizenship - SEMASC, aiming to investigate the management and planning process carried out within the scope of CRAS, whose reference team includes professionals from Social Work. In this way, the research sought to reveal the potential and the existing impasses in the course of planning and its achievement, to offer services to users of the Social Assistance Policy